The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4067/s0717-97072014000400016
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Spectrophotometric Methods for the Determination and Spectroscopic Characterization of Vildagliptin Using Ii -Acceptors in Pharmaceutical Preparations

Abstract: Three simple, quick and sensitive methods are described for the spectrophotometric determination of vildagliptin (VLD) in pharmaceutical preparations. The methods are based on formation of colored charge transfer (CT) complexes between VLD as n-electron donor and chloranilic acid (CA), tetrachloro-1,4-benzoquinone (p-chloranil), 7,7,8,8-tetracyanoquinodimethane (TCNQ) as π-acceptors. The colored products were quantitated spectrophotometrically at 520, 535 and 842 nm for CA, p-chloranil and TCNQ methods, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…It could be taken alone or with other antidiabetic medications 1 . Various methods have been published for the estimation of VIL using UV spectrophotometric 2,3 , spectrofluorimetric 4,5 , liquid chromatographic methods [6][7][8][9][10][11] and voltammetric method 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It could be taken alone or with other antidiabetic medications 1 . Various methods have been published for the estimation of VIL using UV spectrophotometric 2,3 , spectrofluorimetric 4,5 , liquid chromatographic methods [6][7][8][9][10][11] and voltammetric method 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Vildagliptin is not listed in any pharmacopeia. A literature survey revealed that the determination of vildagliptin alone is performed by HPLC in plasma and pharmaceutical formulations , spectrophotometry and spectroflourimetry using the charge transfer complex technique with chloranilic acid, p ‐chloranil and 7,7,8,8‐tetracyanoquinodimethane . Spectrophotometric determinations have been reported using 1,2‐naphthoquinone‐4‐sulfonic acid and 4‐chloro‐7‐nitrobenzofurazan and after reaction with bromocresol green and bromothymol blue .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Development of quantitative analytical method for the estimation of vildagliptin in plasma is very important for studying pharmacokinetic effects and drug-drug interactions. Different analytical methods have been described for the quantification of vildagliptin from formulations and biological samples, including spectrophotometric methods, [6][7] HPLC, [8][9][10][11][12] GC-MS, 13 and capillary electrophoresis. 14 These methods are not sensitive for the quantification in terminal plasma concentration of vildagliptin during pharmacokinetic studies comprising lower dose of vildagliptin.…”
Section: Introductionmentioning
confidence: 99%